Вариант систематизации городищ скифского времени Днепро-Донского лесостепного междуречья - Крютченко, А.А. (Археологія і давня історія України, 2019)
Статья посвящена презентации варианта типологии укрепленных поселений Днепро-Донского
лесостепного междуречья скифского времени. Представленная систематизация городищ основывается на понимании принципов построения их обороны. Искусственные защитные сооружения по их
организации, комбинации и функциональности условно разделено на три группы и шесть подтипов. The article is devoted to the development of a typology
of fortified settlements of the Dnieper-Don foreststeppe
interfluves of the Scythian period. The formation
and development of the fortification in that region
was influenced by the economic opportunities of the
local population, relations with neighboring tribes and
among themselves, under special natural-geographical
conditions. The presented systematization of the hillforts
proceeds from the understanding of the principles
of the construction of their defense. Based on which, we
noticed the following possible pattern of systematization
of fortified settlements. Type I is fortified settlements
with a single-row system without additional protective
pre-walls, regardless of whether the fortification is traced along the entire perimeter or only on the front
side. Type II — single-row settlements with additional reinforcement on the front side. Type ІІІ — settlements
with a single-row system of fortifications, having additional protection from a combination of non-residential
frontiers, complicating the approaches to the entrance to the village site and creating the possibility of leading
flanked fire on the attack. Type IV — monuments protected (often on the front side) by a multi-row system
of fortifications. Type V — settlements with a pronounced main courtyard and a large economic frontier.
By the VI type, we attributed the Belsk hillfort due to its features.